The North African campaign - Military Heritage Institute; Allegro Corporation (Portland, OR : Military Heritage Institute : Allegro Corp., 2013)
"The war for control of North Africa was fought across thousands of square miles of blazing desert and inhospitable terrain. it began on September 13, 1940, when Italian troops invaded Egypt and ended on May 13, 1943, with the surrender of all Axis forcesin Tunisia. For two and a half years, Axis and Allied armies seesawed across North Africa in what was the most dynamic and volatile theater of oeprationsin World War II." -- cover.
Disc 1. From SIDI Barrani to El Alamein (The battle for Egypt, Desert victory and bonus material, Field Marshal Montgomery) -- Disc 2. From El Alamein to Tunis: the British advance -- Disc 3. From Casablanca to Tunis: the American advance.
DVD
Keywords: World War, 1939-1945 -- Campaigns -- Africa, North; Military art and science -- History; Battles -- History